Effect of hydrogen enrichment on performance, combustion, and emission of a methanol fueled SI engine. (16th July 2021) - Nuthan Prasad, B.S.; Pandey, Jayashish Kumar; Kumar, G.N.
Abstract: The study of potentially high rated alternative fuel (Methanol) for the IC engines is an exciting topic in the recent research advancement. However, the study of combination of methanol and hydrogen is considered to address both economic and environmental needs. Hydrogen with best combustion characteristics will compensate for the drawbacks of methanol as a fuel. In the present investigation hydrogen enrichment to methanol has shown a significant enhancement in performance and combustion; the overall emission has reduced substantially. The experiments for a different set of trials, including hydrogen enrichment ranging between 5% and 20% with 2.5% increment, the engine is operated with wide-open throttle (WOT) condition for different speeds. The increase in enrichment of hydrogen has shown a rise in BTE, BP, and a reduced BSEC value. The percentage increase in BTE is between 20 and 30%, and an increase in hydrogen beyond 12.5% would affect the volumetric efficiency, and thus performance declines after that. The exhaust emissions have a huge impact on hydrogen enrichment; CO, HC, and CO2 emission are reduced by 30–40%; however, an increase in cylinder temperature due to rapid combustion slightly increases the NOx emission. Thus hydrogen enriched methanol operating at higher compression ratio can improve the overall engine characteristics significantly. Graphical abstract: Image 1 Highlights: Hydrogen enriched methanol has a better combustion characteristic. Combustion of hydrogen enriched methanol is smooth at CR 14. High octane number and oxygen content are two key factors associated with methanol. The increase in enrichment of hydrogen has shown a rise in BTE, BP, and a reduced BSEC value. The hydrogen enriched methanol fueled SI engine reduces the CO, HC and CO2 emission by 30–40%.